Elijah High Altitude Balloon Launch Team 2012-2013 - Capek, Tyler; Oliphant, Richard; Turner, Devin; Weiland, Danielle (Proceedings of the Wisconsin Space Conference, 2012)
The 2012-2013 launch team of four undergraduate students has brought itself up to speed on the equipment and software necessary for high altitude balloon flights, prepared and tested it all, and completed two successful flights. GPS flight data of latitude, longitude, time, and altitude was collected and analyzed. A new mobile tracking tool was used more than ever before with the growing popularity of smart phones; and new methods were used for data analysis and presentation thanks to technologies now available on the internet.Â